Studies in the Pentateuch - Emerton, John Adney (Supplements to Vetus Testamentum, 1990)
Preliminary material /J.A. Emerton -- Splitting the Adam: The Usage of ʾĀadām In Genesis I-V1 /Richard S. Hess -- The Toledot of Adam /Howard N. Wallace -- The Isles of the Nations: Genesis X and Babylonian Geography /Wayne Horowitz -- The Site of Salem, the City of Melchizedek (Genesis XIV 18) /J.A. Emerton -- Some Problems in Genesis XIV /J.A. Emerton -- Abraham‘s Righteousness (Genesis XV 6) /R.W.L. Moberly -- The Hagar Traditions in Genesis XVI And XXI /T.D. Alexander -- The Elohistic Depiction of Aaron: A Study in the Levite-Zadokite Controversy /Marsha White -- The Wilderness Itineraries and Recent Archaeological Research /G.I. Davies -- The Biblical Dietary Laws and the Concept of Holiness /Edwin Firmage -- \'Yahweh is One\':The Translation of the Shema /R.W.L. Moberly -- Concerning return to Egypt: Deuteronomy XVII 16 And XXVIII 68 Reconsidered /David J. Reimer -- The Creed of Deuteronomy XXVI Revisited /Dwight R. Daniels -- Indexes: Authors Cited /J.A. Emerton -- Reference /J.A. Emerton.